Pharmaceutical care as a historical, normative-legal and social-economic category in the system of the population health and pharmaceutical care - G. L. Panfilova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. Terminological vagueness of the term «pharmaceutical care» in domestic legislative framework and scientific environment makes it impossible to introduce new forms and methods of providing pharmaceutical population in Ukraine effectively. In order to form the unified methodological approach to identify and order the use of the mentioned term, the results of organizational-economic studies in pharmacy and the existing legal framework have been analyzed.